Particulate Matter 2.5 and Hematological Disorders From Dust to Diseases: A Systematic Review of Available Evidence - Fongsodsri, Kamonpan; Chamnanchanunt, Supat; Desakorn, Varunee; Thanachartwet, Vipa; Sahassananda, Duangjai; Rojnuckarin, Ponlapat; Umemura, Tsukuru (Frontiers in Medicine, 2021)
Particulate matter 2.5 (PM2.5) in the air enters the human body by diffusion into the blood. Therefore, hematological abnormalities might occur because of these toxic particles, but few studies on this issue have been reported. According to Cochrane guidance, we performed a systematic review on the relationship between exposure to PM2.5 and the risk of hematological disorders. Ten articles were included in this review. Anemia was found among children and elderly populations with 2- to 5-year PM2.5 exposure. Young children from mothers exposed to air pollution during pregnancy had a higher incidence of leukemia similar to the elderly. Supporting these data, outdoor workers also showed abnormal epigenetic modifications after exposure to very high PM2.5 levels. Adults living in high PM2.5 areas for 2 years were more likely to develop thrombocytosis. Finally, elderly populations with 7- to 8-year PM2.5 exposure showed increased risks of venous thromboembolism. In conclusion, the associations between PM2.5 and hematological aberrations among high-risk people with long-term exposure were reported.